1992
DOI: 10.1084/jem.176.3.781
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage inflammatory protein-1 alpha activates basophils and mast cells.

Abstract: SummaryMacrophage inflammatory protein-1 (MIP) is a recently cloned cytokine that causes neutrophilic infiltration and induces an inflammatory response. We studied the effect of MIP-lo~ on histamine secretion from basophils and mast cells. Leukocytes from allergic and normal subjects were studied. MIP-loe caused dose-dependent release of histamine from basophils of 14 of 20 allergic donors at concentrations of 10-9-10 -7 M, and the mean release was 13.50 + 2.9% at the highest concentration. In the same experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
76
1

Year Published

1993
1993
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(83 citation statements)
references
References 24 publications
6
76
1
Order By: Relevance
“…CCL3 was reported to stimulate human mast cell degranulation in vitro (16) and murine mast cell degranulation in vitro and in vivo (7,17). We found that treatment of mast cells with CCL3 and Ag results in greater degranulation than does cross-linking of FcεRI alone (8,17).…”
mentioning
confidence: 55%
“…CCL3 was reported to stimulate human mast cell degranulation in vitro (16) and murine mast cell degranulation in vitro and in vivo (7,17). We found that treatment of mast cells with CCL3 and Ag results in greater degranulation than does cross-linking of FcεRI alone (8,17).…”
mentioning
confidence: 55%
“…CCL3, a C-C chemokine, can chemoattract neutrophils, monocytes, eosinophils, basophils, and lymphocytes, and is a ligand for both CCR1 and CCR5 [44][45][46][47][48]. CCL3 caused a dose-dependent increase in neutrophil recruitment in a dinitrofluorobenzene-induced contact hypersensitivity model [49].…”
Section: Discussionmentioning
confidence: 99%
“…Such influences have primarily been attributed to the biological effects of T cellderived soluble mediators on mast cell function (38,39). However, recent investigations of mast cell-T cell interactions have revealed a novel intercellular communication exclusively involving the binding of cell surface molecules.…”
Section: Discussionmentioning
confidence: 99%